Diagnostic yield of endoscopic ultrasound-guided tissue acquisition of solid pancreatic lesions after inconclusive percutaneous ultrasound-guided tissue acquisition. (1st September 2020) - Le Grazie, Marco; Conti Bellocchi, Maria Cristina; Bernardoni, Laura; Fusaroli, Pietro; Manfrin, Erminia; Pallio, Socrate; Gabbrielli, Armando; Crinò, Stefano Francesco
Abstract: Introduction: After a failed percutaneous ultrasound (US)-guided sampling, it is recommended that endoscopic ultrasound (EUS)-guided tissue acquisition (TA) be performed for non-resectable solid pancreatic lesions according to the European Federation of Societies for Ultrasound in Medicine and Biology. However, the diagnostic performance of EUS-guided TA in this setting is unknown. Methods: We retrospectively analyzed the performance and safety of EUS-guided TA in patients with a previous failed percutaneous biopsy. We also evaluated the diagnostic delays between the percutaneous approach and EUS diagnosis. Results: Over a period of 2 years, 49 patients were identified (29 males, mean age 65 years). The reasons for failure of percutaneous sampling were inadequate samples in 25 (52.1%) cases and lesions that were not visible or targetable in 24 (47.9%) cases. In one case, EUS-guided TA was not performed because of the interposition of a metallic biliary stent. No adverse events were recorded for both the percutaneous and EUS approaches. The median diagnostic delay was 12 days. Overall, the sensitivity and accuracy of EUS-guided TA were 92.7 and 93.7%, respectively. A subgroup analysis examined cases with inadequate samples obtained with the percutaneous approach, and the sensitivity and accuracy of EUS-guided TA were 85.7 and 88%, respectively. Conclusion: EUS-guided TA is safe and accurate for the diagnosis of pancreatic lesions after a previous inconclusive percutaneous approach.